1986
DOI: 10.1148/radiology.161.1.3763864
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral hemangiomas: radiologic evaluation.

Abstract: Radiologic studies of 57 solitary vertebral hemangiomas (VHs) were reviewed to find radiographic and computed tomographic (CT) criteria by which to distinguish asymptomatic lesions from those compressing the spinal cord. Six features were seen significantly more often in those compressing the cord: location between T-3 and T-9, involvement of the entire vertebral body, extension to the neural arch, an expanded cortex with indistinct margins, an irregular honeycomb pattern, and soft-tissue mass. Contrast materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
154
1
14

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 0 publications
2
154
1
14
Order By: Relevance
“…Diagnosis of asymptomatic lesions is commonly an incidental finding on spinal radiological investigations. However, the features displayed on angiography, CT, or MR imaging may differ between asymptomatic lesions, which possess normal or slightly increased vascularity, and symptomatic lesions, which show moderate to intense hypervascularity [16,26]. Due to their increased blood flow, symptomatic cavernous malformations may expand in vertebral bodies, producing bony erosion in some areas and reactive vertical trabeculation in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of asymptomatic lesions is commonly an incidental finding on spinal radiological investigations. However, the features displayed on angiography, CT, or MR imaging may differ between asymptomatic lesions, which possess normal or slightly increased vascularity, and symptomatic lesions, which show moderate to intense hypervascularity [16,26]. Due to their increased blood flow, symptomatic cavernous malformations may expand in vertebral bodies, producing bony erosion in some areas and reactive vertical trabeculation in others.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their increased blood flow, symptomatic cavernous malformations may expand in vertebral bodies, producing bony erosion in some areas and reactive vertical trabeculation in others. On plain radiographs, vertebral bodies may display coarse vertical striations [ 12,16], while on CT they present a "polka dot" appearance [8]. Angiography is essential in the diagnosis of vertebral cavernous malformations, and MR imaging may delineate their extraosseous components better than CT [28].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic hemangiomas require adequate treatment, such as radiation, embolization, vertebroplasty, or surgical resection. 7) Laminectomy or anterior corpectomy with a strut graft is often recommended, particularly for vertebral hemangiomas with extraosseous extension into the vertebral canal. 2) Adequate decompression and vertebral stability during such open surgery are indispensable for neurological improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In radiologic evaluation of vertebral hemangiomas, Laredo et al [5] described six features which were seen significantly more often in symptomatic vertebral hemangioma: location between D3 and D9, involvement of the entire vertebral body, extension to the neural arch, an expanded cortex with indistinct margins, an irregular honeycomb pattern, and soft tissue mass. They also suggested that fatty vertebral hemangioma may represent inactive form while soft tissue content at CT and low signal at MRI may indicate a more active vascular lesion with potential to compress the spinal cord.…”
Section: Discussionmentioning
confidence: 99%